Modernity of tradition: political development in India - Rudolph,Lloyd I.; Rudolph, Susanne Hoeber (New Delhi, 1999)
The modernity of tradition, now a classic text in the fields of sociology and political science has greatly influenced our understanding of political development in a tradition-bound society like India. When it was first published, 'tradition' and 'modernity' were generally seen as opposed categories. By showing that caste groups (and other traditional ascriptive groups) reassert their identity in different modern contexts in new ways, the Rudolphs' book opened up new ways of looking at and understanding the complexities of political development and social change in India.
Keywords: Social anthropology